Supramolecular Copolymerization of Bichromophoric Chiral and Achiral Perylenediimide Dyes - Yonezawa, Shumpei; Kawai, Tsuyoshi; Nakashima, Takuya (Frontiers in Chemistry, 2021)
Propagation and amplification of chirality are considered to play an important role in the chemical evolution of biological homochirality. Stereochemical communications have been demonstrated to have a significant effect on the formation of chiral hierarchical structures in helical polymers, surface assemblies and supramolecular polymers. The formation of supramolecular copolymers based on chiral and achiral bichromophoric perylenediimide (PDI) dyes having a binaphtyl- and biphenyl-core-bridging unit, respectively, was investigated in terms of chiral amplification and propagation. The biphenyl-bridged PDI dye was expected to perform as a prochiral component to adopt both right- and left-handed twisting structures with the free rotation over the phenyl-phenyl linkage upon partnered with the chiral binaphtly-PDI dye in the coassemblies. The coassemblies between the chiral and achiral PDI dyes with dissimilar core units demonstrated the composition dependent control in the length of supramolecular nanofibers as well as amplification of optical activity.